Mitochondria on the move: Horizontal mitochondrial transfer in disease and health - Dong, Lan-Feng; Rohlena, Jakub; Zobalova, Renata; Nahacka, Zuzana; Rodriguez, Anne-Marie; Berridge, Michael V; Neuzil, Jiri (The Journal of cell biology, 2023)
Mammalian genes were long thought to be constrained within somatic cells in most cell types. This concept was challenged recently when cellular organelles including mitochondria were shown to move between mammalian cells in culture via cytoplasmic bridges. Recent research in animals indicates transfer of mitochondria in cancer and during lung injury in vivo, with considerable functional consequences. Since these pioneering discoveries, many studies have confirmed horizontal mitochondrial transfer (HMT) in vivo, and its functional characteristics and consequences have been described. Additional support for this phenomenon has come from phylogenetic studies. Apparently, mitochondrial trafficking between cells occurs more frequently than previously thought and contributes to diverse processes including bioenergetic crosstalk and homeostasis, disease treatment and recovery, and development of resistance to cancer therapy. Here we highlight current knowledge of HMT between cells, focusing primarily on in vivo systems, and contend that this process is not only (patho)physiologically relevant, but also can be exploited for the design of novel therapeutic approaches.